Human Resources in Education: Training and Work Motivation on Teacher Performance - Zulfina Adriani; Nurul Hikmah (Universitas Jambi, Indonesia, 2022)
It seems unquestionable that education matters for human and economic development and the roles of teachers in classroom are very important for producing good human resources in terms of student achievement. This study aimed to determine the effect of training and work motivation on teacher performance in one junior high school in Jambi, Indonesia. The respondents in this study were 13 employees. In collecting the data, questionnaires were used with a Likert scale. The data analysis technique in this study used an analytical tool, namely SPSS Version 25. The results indicated that (1) partially training had a significant positive effect on teacher performance, (2) partially work motivation had a significant positive effect on teacher performance, and (3) simultaneously training and work motivation had a significant effect on teacher performance. Implications of findings are discussed.